IMPLEMENTATION OF THE ELECTRONIC TICKETING SYSTEM POLICY IN IMPROVING THE ORDER OF ROAD USERS IN BANJARMASIN CITY - Murakhman Sayuti Enggok; Normajatun (International Journal of Social Science, 2024)
This research is intended to determine the implementation of policiesElectronic Traffic Law Enforcement and what are the inhibiting factors for the implementation of this policy in the City of Banjarmasin.This study uses a qualitative approach. The data analysis technique was carried out descriptively. The results of the study show that although there are still obstacles such as:socialization is not yet widespread throughout the city of Banjarmasin, facilities and infrastructure are not supportive, there are still people who are not orderly in traffic and cultural factors of the local community. butpolicyElectronic Traffic Law EnforcementinBanjarmasin City is measured from the variables of communication, resources, disposition and bureaucratic structure it has been well implemented but not optimal.